CRISPR/dCas9-Mediated Parkin Inhibition Impairs Mitophagy and Aggravates Apoptosis of Rat Nucleus Pulposus Cells Under Oxidative Stress - Lan, Tao; Zheng, Yu-chen; Li, Ning-dao; Chen, Xiao-sheng; Shen, Zhe; Yan, Bin (Frontiers in Molecular Biosciences, 2021)
Objective: The aim of this study is to expore the role of Parkin in intervertebral disc degeneration (IDD) as well as its mitophagy regulation mechanism. Study Design and Methods: Rat nucleus pulposus cells were stimulated with H2O2 to mimic pathological condition. Apoptosis and mitophagy were assessed by western blot, TUNEL assay, and immunofluorescence staining. CRISPR-dCas9-KRAB system was used to silence the expression of Parkin. Result: In this study we found that Parkin was downregulated in rat NP cells under oxidative stress. In addition, H2O2 resulted in mitochondrial dysfunction, autophagy inhibition and a significant increase of NP cells apoptosis. Meanwhile, Mitophagy inhibition enhanced H2O2-induced apoptosis. Furthermore, repression of Parkin significantly attenuated mitophagy and exacerbated apoptosis. Conclusion: These results suggested that Parkin may play a protective role in alleviating NP cells apoptosis via mitophagy and targeting Parkin may provide a promising therapeutic strategy for preventing IDD.